Conservation of position and sequence of a novel, widely expressed gene containing the major human alpha-globin regulatory element. - Vyas, P; Vickers, M; Picketts, D; Higgs, D (1995)
We have determined the cDNA and genomic structure of a gene (-14 gene) that lies adjacent to the human alpha-globin cluster. Although it is expressed in a wide range of cell lines and tissues, a previously described erythroid-specific regulatory element that controls expression of the alpha-globin genes lies within intron 5 of this gene. Analysis of the -14 gene promoter shows that it is GC rich and associated with a constitutively expressed DNase 1 hypersensitive site; unlike the alpha-globin promoter, it does not contain a TATA or CCAAT box. These and other differences in promoter structure may explain why the erythroid regulatory element interacts specifically with the alpha-globin promoters and not the -14 gene promoter, which lies between the alpha promoters and their regulatory element. Interspecies comparisons demonstrate that the sequence and location of the -14 gene adjacent to the alpha cluster have been maintained since the bird/mammal divergence, 270 million years ago.